One‐Pot Synthesis and Antiproliferative Activity of Highly Functionalized Pyrazole Derivatives. (28th January 2022) - Lusardi, Matteo; Rotolo, Chiara; Ponassi, Marco; Iervasi, Erika; Rosano, Camillo; Spallarossa, Andrea
Abstract: A series of highly functionalized pyrazole derivatives has been prepared by a one‐pot, versatile and regioselective procedure. Pyrazoles 1 –29 were tested in cell‐based assay to assess their antiproliferative activity against a panel of tumour cells. Additionally, the cytotoxicity of prepared compounds was evaluated against normal human fibroblasts. The antiproliferative activity of the synthesized molecules emerged to be affected by the nature of the substituents of the pyrazole scaffold and derivatives 21 –23 proved to inhibit the growth of melanoma and cervical cancer cells. Compound 23 was identified as the most active derivative and docking simulations predicted its ability to interact with estrogen receptors. Abstract : A one‐pot, regioselective and versatile procedure was developed for the synthesis of a series of highly functionalized pyrazole derivatives. The compounds were tested for antiproliferative activity on a panel of tumour and normal cells. 5‐anilino‐4‐nitrile‐3‐phenyl pyrazoles emerged as the most promising derivatives, and compound 23 selectively inhibited the growth of estrogen‐dependent SKMEL‐28 and HeLa cells. Docking simulations calculated micromolar K i values for the ERα‐23 and ERβ‐23 complexes, suggesting estrogen receptors as potential biological targets for this series of pyrazoles.